Towards Better Financial Governance: The Urgency of Model Risk Management in Indonesia Viewed Through Maqashid Shariah - Ferdinand, Novingky (International Journal of Economics (IJEC), 2024)
This study assesses the adequacy of Model Risk Management (MRM) frameworks within Indonesian Islamic banking by utilizing Maqashid Shariah principles as a tool to align these frameworks more closely with global standards, specifically focusing on safeguarding life (Hifzh Al-Nafs) and property (Hifzh Al-Mal). Through a comparative literature review, this research examines the structure and effectiveness of MRM practices in Indonesia, referencing regulations such as POJK 65/2016 and SEOJK 25-SEOJK.03-2023, against those in developed financial markets such as the USA, UK, Europe, Japan, and UAE, with an emphasis on governance, lifecycle management, and internal audit processes. The findings suggest that Indonesia’s current MRM frameworks are somewhat rudimentary when contrasted with international norms. Key areas identified for enhancement include expanding the scope, enhancing governance structures, refining model lifecycle management, and strengthening internal audits and oversight mechanisms. By employing Maqashid Shariah principles as an analytical tool, this paper proposes enhancements to MRM frameworks that can significantly improve the stability and compliance of Islamic banks in Indonesia, promoting greater global competitiveness and adherence to Shariah principles. This approach not only integrates traditional MRM approaches with Islamic ethical standards but also provides a tailored framework for regulatory enhancements that support a stable, compliant, and ethical Islamic banking environment.